Etos Kerja Mama-Mama Suku Mee sebagai Pedagang Noken di Kota Jayapura - Rosita Hommy; Gerdha K.I. Numberi; Marlina Flassy (CENDERAWASIH: Jurnal Antropologi Papua, 2022)
This research aims to find out how the work ethics of women vendors selling Noken Tribe Mee around Saga Mall Abepura, Kota Baru District is in 2022. This research uses a qualitative research method, this method seeks to understand and interpret the meaning of an event involving human behavior in certain situations. The sampling technique used in this research uses purposive sampling technique. Data collection was done through observational literature studies, in-depth interviews, snowballing documentation. Data analysis techniques include stages of data reduction, data presentation and drawing conclusions. The results of the research show that the work ethics of the women of the Mee Tribe noken sellers around Saga Mall Abepura, Kota Baru Subdistrict is seen in how they work by respecting time, choosing selling materials, serving customers or consumers, choosing a place to sell. The influence of the cultural values of the Mee Tribe mothers is very strong and has been a tradition passed down from generation to generation and has religious values or a strong belief in the Creator.